Root cause analysis of evaporator tubes failure of a HRSG unit. (March 2019) - Gupta, Jeetendra; Kujur, Abhay; Talukdar, Maushmi K.; Velusshami, S.K.; Prasad, Sangeeta R.; Bhatia, Bharti; Sharma, Anita; Bhardwaj, Anil
Highlights: Failure of evaporator tube before completing its design life. In service microstructure degradation of evaporator tube material. Formation of creep voids & creep cracks, which led to grain separation.